(3GdebOeI GdLRQjI aj Yde GdJLhjOs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , (B833 (3g`s
(3ChdgG (B:s
(3jbhd QGLj Yah QH SGeY eMeO Hf GdLRQj GdTGaYj GdMeO ddg hUdi Gddg Ydi fHjg heUWaGg eMeO hBdg hUMHg hebQF GdbQBf eY eMHgs
(3BNQgG (B:s
(3hbO JbOe fXei GdebOeg efi dbGQF GdbQBf JbOeg (B- (3hGdMeO ddg dgG NJGe Ke GdUdGI HYO hGdSdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 45s
(3eYLe GdeDdajf (B3 / 687s
(3cTa GdXfhf (B2 / 1799s
(3TPQGJ GdPgH (B7 / 204s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs